Electroacupuncture Alleviates Cerebral Ischemia/Reperfusion Injury in Rats by Histone H4 Lysine 16 Acetylation-Mediated Autophagy - Xu, Shu-Ying; Lv, He-Qun; Li, Wen-Qian; Hong, Hao; Peng, Yong-Jun; Zhu, Bing-Mei (Frontiers in Psychiatry, 2020)
Background: Electroacupuncture (EA) treatment in ischemic stroke has been highlighted recently; however, the specific mechanism is still elusive. Autophagy is considered a new target for cerebral ischemia/reperfusion (I/R), but whether it plays a role of protecting or causing rapid cell apoptosis remains unclear. Studies have reported that the reduction in lysine 16 of histone H4 acetylation coheres with autophagy induction. The primary purpose of the study was to explore whether EA could alleviate I/R via autophagy-mediated histone H4 lysine 16 acetylation in the middle cerebral artery occlusion (MCAO) rat model. Methods: One hundred and twenty male Sprague-Dawley rats were divided into five groups: control group, MCAO group, MCAO+EA group, MCAO+EA+hMOF siRNA group, and MCAO+EA+Sirt1 inhibitor group. EA was applied to “Baihui” (Du20) and “Renzhong” (Du26) at 5 min after modeling and 16 h after the first EA intervention. The structure and molecular markers of the rat brain were evaluated. Results: EA significantly alleviated I/R injury by upregulating the expressions of Sirt1, Beclin1, and LC3-II and downregulating the expressions of hMOF and H4K16ac. In contrast, the Sirt1 inhibitor lowered the increase in Sirt1, Beclin1, and LC3-II and enhanced the level of hMOF and H4K16ac expressions associated with EA treatment. Besides, ChIP assay revealed that the binding of H4K16ac in the Beclin1 promoter region of the autophagy target gene was significantly raised in the MCAO+EA group and MCAO+EA+hMOF siRNA group. Conclusions: EA treatment inhibited the H4K16ac process, facilitated autophagy, and alleviated I/R injury. These findings suggested that regulating histone H4 lysine 16 acetylation-mediated autophagy may be a key mechanism of EA at Du20 and Du26 to treat I/R.